Working Memory Training in Amnestic and Non-amnestic Patients With Mild Cognitive Impairment: Preliminary Findings From Genotype Variants on Training Effects - Hernes, Susanne S.; Flak, Marianne M.; Løhaugen, Gro C. C.; Skranes, Jon; Hol, Haakon R.; Madsen, Bengt-Ove; Knapskog, Anne-Brita; Engvig, Andreas; Pripp, Are; Ulstein, Ingun; Lona, Trine; Zhang, Xin; et al. (Frontiers in Aging Neuroscience, 2021)
Working memory training (WMT) effects may be modulated by mild cognitive impairment (MCI) subtypes, and variations in APOE-epsilon (APOE-) and LMX1A genotypes. 61 individuals (41 men/20 women, mean age 66 years) diagnosed with MCI (31 amnestic/30 non-amnestic) and genotyped for APOE- and LMX1A completed 4 weeks/20-25 sessions of WMT. Cognitive functions were assessed before, four weeks and 16 weeks after WMT. Except for Processing Speed, the non-amnestic MCI group (naMCI) outperformed the amnestic MCI (aMCI) group in all cognitive domains across all time-points. At four weeks, working memory function improved in both groups (p<0.0001), but at 16 weeks the effects only remained in the naMCI group. Better performance was found after training for the naMCI patients with LMX1A-AA genotype and for the APOE-4 carriers. Only the naMCI-APOE-4 group showed improved Executive Function at 16 weeks. WMT improved working memory and some non-trained cognitive functions in individuals with MCI. The naMCI group had greater training gain than aMCI group, especially in those with LMX1A-AA genotype and among APOE-ε4-carriers. Further research with larger sample sizes for the subgroups and longer follow-up evaluations is warranted.